Hemoperitoneum in a Cow with Lumbar Muscle Hemangiosarcoma - de Menezes, Islaine Silva; Freitas, Cassiane Barroso; Pereira, Gabriela Oliveira; Pereira, Asheley Henrique Barbosa; Albuquerque, Celina Vieira; Pimenta, Maria Carolina Neves; de Souza, Bruno Gonçalves; Ubiali, Daniel Guimarães (Acta Scientiae Veterinariae, 2022)
Background: Hemangiosarcoma is a malignant neoplasm of endothelial cells with an infiltrative growth pattern. Hemangiosarcomas are frequently reported in canines and rare in felines, sheep, goats, swine, horses and cattle. Few cases of hemangiosarcoma were reported in cattle. In the present report, we describe the clinicopathological findings of a bovine muscle hemangiosarcoma. Case: A 6-year-old, Girolando cow from the Dairy Cattle Sector of the Federal Rural University of Rio de Janeiro (UFRRJ), Seropédica, presented sternal decubitus. Clinical signs were markedly pale mucous membranes, moderate dehydration, respiratory distress, and increased heart rate. The hematological examination revealed intense regenerative anemia. Due to the worsening of the clinical condition, the cow was submitted to euthanasia. The necropsy and collection of various fragments of organs were performed, which were sent to the “Setor de Anatomia Patológica” (SAP-UFRRJ). Tissues were fixed in 10 % buffered formalin, routinely processed for histology and stained with Hematoxylin and Eosin (HE). The external mucous membranes were markedly pale. Multifocal areas of 1.5 x 1.0 cm, irregular and dark red were observed dissecting the quadratus lumborum muscle (hemangiosarcoma) fibers. These neoplasms were associated with an extensive cruoric clot adhered to the muscle fibers. The extensive, red, friable mass measured approximately 76 x 55 x 20 cm on the serous surfaces of the organs of the peritoneal cavity (hemoperitoneum). The spleen was moderately reduced. The bone marrow was markedly pale. Histologically, it was observed that there was an extensive proliferation of endothelial cells in the quadratus lumbar muscle mass dissecting the epimysium and perimysium. Endothelial cells had moderate pleomorphism, organized in vascular channels and forming multifocally solid areas with a significant amount of eosinophilic fibrillar material (fibrin). Sections of muscle neoplasm were subjected to immunohistochemistry with anti-von Willebrand factor primary antibody, which showed a multifocal moderate cytoplasmic immunolabeling of neoplastic endothelial cells. Discussion: There are few reports of striated muscle hemangiosarcoma in cattle. Muscular hemangiosarcomas were reported in a 4-month-old calf in the left cervical trapezius muscle and a 6-year-old Holstein cow with left pelvic limb mass lateral and distal to the knee. Some reports presented hemangiosarcoma in the iliopsoas muscle, left cervical trapezius muscle, pelvic limb muscles and right cervical muscle of the bovine. In the presented report, hemoperitoneum occurred as a result of hemorrhages from muscle hemangiosarcoma. Other studies have demonstrated cavity hemorrhages in joint, pelvic, pleural and cranial cavities associated with hemangiosarcoma. Hemangiosarcoma with regenerative anemia must be distinguished from other diseases that cause anemia. The main differential diagnoses of bovine with anemia are vena cava syndrome, coumarin derivatives poisoning, acute poisoning by Pteridium spp., tick fever, anaplasmosis, babesiosis and trypanosomiasis. Hemangiosarcoma should be differentiated from other lesions as hemangioma, vascular tumor of lymphatic endothelium and perivascular wall tumors. Cases with poorly differentiated morphology should be submitted for immunohistochemistry. In the present hemangiosarcoma case, we have used the von Willebrand factor for immunohistochemistry diagnosis. Expression of angiogenic growth factors such as CD31, vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF) and angiopoietin-1 (Ang-1) have also been used in the diagnosis of vascular proliferation lesions. Hemangiosarcoma in cattle should be included mainly in the differential diagnosis of diseases that cause acute anemia in cattle. Keywords: cattle, neoplasia, hemangiosarcoma, hemoperitoneum, anemia.